2018
DOI: 10.1063/1.5049783
|View full text |Cite
|
Sign up to set email alerts
|

Black phosphorus with a unique rectangular shape and its anisotropic properties

Abstract: Black Phosphorus (BP) is a 2D material with high hole mobility. However, due to its fast degradation property under ambient air, fast crystal orientation determination is required for the fabrication of BP transistor along the crystal orientation with the highest mobility. In this paper, a method for producing BP flakes with a special rectangular shape was developed. This shape provides important information about the crystal orientation of BP. By using polarized Raman measurements, it was demonstrated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Determination of the structural and chemical stability of layered black phosphorus (BP) under varying temperature T and pressure p remains a major challenge for its implementation in any proposed device application. The structural stability of BP can be probed by X-ray diffraction or Raman spectroscopy under high-pressure conditions, where Raman spectroscopy provides the advantage of identifying the locally induced strains and structural phase transitions from the shift in peak positions. Recent studies on the pressure-dependent Raman spectra of layered BP flakes have revealed the possibility of phase transitions under high-pressure conditions, which suggests a possible pressure-induced transition from pristine orthorhombic (BP) to rhombohedral crystal structure (blue phosphorus, bP) under a pressure ∼4.7 GPa followed by simple cubic system under ∼11 GPa at room temperature. At ambient pressure, BP crystallizes in an orthorhombic (A17) structure (space group Cmce , no. 64, point group D 2h ) with a density of ∼2.7 g cm –1 , where atoms are configured in a puckered atomic arrangement with AB stacking (Figure a). , The puckered atomic structure of BP leads to a pronounced anisotropy in electronic, optical, and vibrational properties. Once the structural phase transition takes place under high pressure, the pristine orthorhombic crystal transforms into a rhombohedral (A7) crystal, with ABC-type layer stacking (space group R3̅m , no. 166, point group D 3d ) of density ∼3.2 g cm –1 , which is comparatively higher than that of BP (Figure b) .…”
Section: Introductionmentioning
confidence: 99%
“…Determination of the structural and chemical stability of layered black phosphorus (BP) under varying temperature T and pressure p remains a major challenge for its implementation in any proposed device application. The structural stability of BP can be probed by X-ray diffraction or Raman spectroscopy under high-pressure conditions, where Raman spectroscopy provides the advantage of identifying the locally induced strains and structural phase transitions from the shift in peak positions. Recent studies on the pressure-dependent Raman spectra of layered BP flakes have revealed the possibility of phase transitions under high-pressure conditions, which suggests a possible pressure-induced transition from pristine orthorhombic (BP) to rhombohedral crystal structure (blue phosphorus, bP) under a pressure ∼4.7 GPa followed by simple cubic system under ∼11 GPa at room temperature. At ambient pressure, BP crystallizes in an orthorhombic (A17) structure (space group Cmce , no. 64, point group D 2h ) with a density of ∼2.7 g cm –1 , where atoms are configured in a puckered atomic arrangement with AB stacking (Figure a). , The puckered atomic structure of BP leads to a pronounced anisotropy in electronic, optical, and vibrational properties. Once the structural phase transition takes place under high pressure, the pristine orthorhombic crystal transforms into a rhombohedral (A7) crystal, with ABC-type layer stacking (space group R3̅m , no. 166, point group D 3d ) of density ∼3.2 g cm –1 , which is comparatively higher than that of BP (Figure b) .…”
Section: Introductionmentioning
confidence: 99%
“…The armchair and zigzag axes cannot be distinguished from the intensity of any of the Raman peaks alone, as the polarization behavior of each peak depends strongly on the excitation wavelength and the flake thickness . However, for 532 nm excitation and all thicknesses, the ratio of the intensities of the A 2 g and the A 1 g Raman peaks is higher for the armchair than the zigzag axis, so this ratio remains a robust way to distinguish between the axes. , Representative Raman spectra are presented for the visible frequency sample on SrTiO 3 in Figure e.…”
mentioning
confidence: 99%
“…43 However, for 532 nm excitation and all thicknesses, the ratio of the intensities of the A 2 g and the A 1 g Raman peaks is higher for the armchair than the zigzag axis, so this ratio remains a robust way to distinguish between the axes. 43,44 Representative Raman spectra are presented for the visible frequency sample on SrTiO 3 in Figure 1e.…”
mentioning
confidence: 99%